2017
DOI: 10.1097/adm.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron Does Not Reduce Withdrawal in Patients With Physical Dependence on Chronic Opioid Therapy

Abstract: Objectives Individuals taking opioids for an extended period of time may become physically dependent, and will therefore experience opioid withdrawal should they stop taking the medication. Previous work in animal and human models has shown that the serotonin (5-HT3) receptor may be implicated in opioid withdrawal. In this study, we investigated if ondansetron, a 5-HT3-receptor antagonist, could reduce the symptoms of opioid withdrawal after chronic opioid exposure in humans. Methods In this double-blinded, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…For instance, a recent study in a human OUD clinical population showed that response to a precipitated naloxone challenge was significantly associated with withdrawal response in a subsequent double-blind randomized and controlled pharmacotherapy examination (Dunn et al, 2018b). A human laboratory model was also used in some of the empirical human studies reviewed herein (Bisaga et al, 2001;Jain et al, 2011;Chu et al, 2017) and has been regularly used to screen medications for alcohol and tobacco use disorders (Perkins et al, 2008(Perkins et al, , 2013McKee, 2009;McKee et al, 2012). Together, this evidence suggests that a laboratory model could be a promising method for screening candidate opioid withdrawal medications prior to clinical trial investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a recent study in a human OUD clinical population showed that response to a precipitated naloxone challenge was significantly associated with withdrawal response in a subsequent double-blind randomized and controlled pharmacotherapy examination (Dunn et al, 2018b). A human laboratory model was also used in some of the empirical human studies reviewed herein (Bisaga et al, 2001;Jain et al, 2011;Chu et al, 2017) and has been regularly used to screen medications for alcohol and tobacco use disorders (Perkins et al, 2008(Perkins et al, , 2013McKee, 2009;McKee et al, 2012). Together, this evidence suggests that a laboratory model could be a promising method for screening candidate opioid withdrawal medications prior to clinical trial investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported on whether the 5-HT 3 antagonist ondansetron modifies opioid withdrawal severity in humans. The first was a case report that suggested ondansetron might reduce human opioid withdrawal syndrome severity (Wakim, 2012); however, the second was a placebo-controlled within-subject empirical evaluation that found no benefit of ondansetron relative to placebo following naloxone-precipitated withdrawal (Chu et al, 2017).…”
Section: Serotonin Systemmentioning
confidence: 99%
“…5-HT 3 receptor antagonists are also useful in treating alcohol dependence [ 22 , 41 , 238 , 239 , 240 ] but show little clinical usefulness in treating dependencies on other drugs of abuse [ 18 , 241 ]. Since 5-HT 3 receptors are present in the reward center [ 242 ], this differential is unexpected.…”
Section: Current Clinically Used 5-ht 3 Receptor-based Therapiesmentioning
confidence: 99%
“…A recent study (Chu et al, 2017) in The Journal of Addiction Medicine indicated that ondansetron administration did not reduce naloxone-precipitated opiate withdrawal ( NPOW ) symptoms in chronic opiate users with chronic back pain ( COU/CBP ). However, a study design flaw is responsible for the lack of efficacy, which prevents drawing any conclusions from its results.…”
Section: Dear Dr Saitzmentioning
confidence: 99%
“…The anti-emetic effect of ondansetron has a rapid onset (<0.5 hour) because it is mediated at sites (5-HTR3 receptor + vagal afferent nerves in the gastrointestinal tract and brainstem) outside of the CNS (Tyers, 1992; Tyers and Freeman, 1992). This was cited (Chu et al, 2017) as a justification for administering naloxone 0.5 hour after ondansetron treatment. However, ondansetron’s effect on NPOW occurs within the CNS (Chu et al, 2009); a peripheral acting opioid antagonist (methynaltrexone) does not precipitate withdrawal (Portenoy et al, 2008; Thomas et al, 2008).…”
Section: Dear Dr Saitzmentioning
confidence: 99%